Combination of platelet rich plasma and stromal vascular fraction on the level of vascular endothelial growth factor in rat subjects experiencing deep dermal burn injury - Sachraswaty Rachman Laidding, Sachraswaty (Elsevier BV., 2021)
A B S T R A C T Background: The healing process of burns includes coagulation, inflammation, and remodeling. Vascular endo- thelial growth factor (VEGF) is involved throughout this healing process. Stem cells from the platelet-rich plasma (PRP) with stromal vascular fraction (SVF) can increase concentrations of growth factors, including VEGF. This is expected to accelerate burn healing. The aim of this study was to determine the effect of a combination of PRP and SVF on VEGF levels in a rats model of deep dermal burn wound healing. Materials and methods: This is an experimental research study in rats using a post-test control group design with 4 groups: A) control, B) Vaseline, C) topical PRP and SVF, and D) PRP and SVF injection. Burn wounds were induced according to the modified Guo method. Results: In a rats model of deep dermal wound healing, topical Vaseline significantly increased serum VEGF compared to control. Topical application and injection of stem cells also significantly increased serum VEGF compared to control and Vaseline. The VEGF concentration was significantly higher following injection of PRP and SVF, suggesting that the injection route is more effective at increasing VEGF levels compared to the topical application of stem cells. Conclusion: The combination of PRP and SVF, either by injection or topical application, can increase VEGF levels during the healing process from deep dermal burns.